Pengaruh Flexible Working Arrangement, Beban Kerja, dan Kepuasan Kerja terhadap Turnover Intention Generasi Z - Stefanya, Yemima; Winarto, Jacinta (Jurnal Informatika Ekonomi Bisnis, 2025)
The phenomenon of high turnover intention in generation Z is a serious concern for many companies including in the property industry which has a fast work rhythm and high pressure. Generation Z is known to have unique characteristics in working such as valuing work flexibility, work-life balance, having high expectations of the work environment and changing jobs more quickly. Factors that are thought to influence this tendency include flexible working arrangements, workload and job satisfaction. This study aims to analyze how these three variables influence turnover intention in generation Z employees at a property developer company in Bandung. This study uses an associative quantitative approach with a non-probability sampling technique, namely purposive sampling with a judgment sampling approach where 165 people were used as research samples. This study was analyzed using the Structural Equation Modeling-Partial Least Squares method. The results of the study indicate that flexible working arrangements have a significant negative effect on turnover intention, workload has a significant positive effect on turnover intention and job satisfaction has a significant negative effect. This study contributes to the development of management practices, especially strategies to retain generation Z employees in the dynamic property industry.